Ruthenacycles and Iridacycles as Transfer Hydrogenation Catalysts - Ritleng, Vincent; de Vries, Johannes G. (Molecules (Basel, Switzerland), 2021)
In this review, we describe the synthesis and use in hydrogen transfer reactions of ruthenacycles and iridacycles. The review limits itself to metallacycles where a ligand is bound in bidentate fashion to either ruthenium or iridium via a carbon–metal sigma bond, as well as a dative bond from a heteroatom or an N-heterocyclic carbene. Pincer complexes fall outside the scope. Described are applications in (asymmetric) transfer hydrogenation of aldehydes, ketones, and imines, as well as reductive aminations. Oxidation reactions, i.e., classical Oppenauer oxidation, which is the reverse of transfer hydrogenation, as well as dehydrogenations and oxidations with oxygen, are described. Racemizations of alcohols and secondary amines are also catalyzed by ruthenacycles and iridacycles.